Identification and comparative expression analysis of odorant-binding proteins in the reproductive system and antennae of Athetis dissimilis - Yue-Qin Song (Nature Portfolio, 2021)
Abstract Odorant-binding proteins (OBPs) are prevalent in the antennal transcriptomes of different orders of insects. Studies on OBPs have focused on their role in the insect chemosensory system, but knowledge of their functions in the insect testis is limited. We sequenced the transcriptomes of the Athetis dissimilis reproductive organs and analyzed the expression of AdisOBP genes in different tissues. We identified 23 OBPs in the testis and ovaries and 31 OBPs in antennal transcriptomes. The results of real-time quantitative PCR revealed that 23 of the 54 OBP genes were highly expressed in both female and male antennae, including three that exhibited male-biased expression and 15 that exhibited female-biased expression. A total of 24 OBPs were highly expressed in the testis of A. dissimilis, while expression of OBPs in the ovaries was very low. These findings highlight the functional diversity of OBPs in insects and can facilitate further studies on the OBPs in A. dissimilis and lepidopteran species.